Pemanfaatan Teknologi Informasi dan Komunikasi pada Lingkungan Pemerintahan Desa di Kecamatan Sungai Pandan - Harja Santana Purba; Ati Sukmawati; Muhammad Hifdzi Adini; Delsika Pramata Sari (Universitas Lambung Mangkurat, 2018)
The purpose of this study was to know the infrastructure and utilization of Information and Communication Technology (ICT) in village government in Sungai Pandan Subdistrict. The study was done by making mapping based on the existing potentials in ICT which was then compared with the results of implementation and resources that were in the village government. Data collection techniques in this study used questionnaire and interview. The ICT utilization survey was conducted in 17 village in Sungai Pandan subdistrict. Based on survey results, all villages had used computers to perform routine administrative work. Common applications used are Microsoft Office. In addition to general applications used are SIMDA and SisKeuDes for financial management. There were only two villages that have adequate internet facilities, while other villages were still using the internet sourced from personal cell phones. Kata kunci : survey, utilization of ICT, village administration